2007
DOI: 10.2337/db06-1065
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Effects of Rosiglitazone and Exercise in the Treatment of Lipid-Induced Insulin Resistance

Abstract: Both pharmacological intervention (i.e., thiazolidinediones [TZDs]) and lifestyle modification (i.e., exercise training) are clinically effective treatments for improving whole-body insulin sensitivity. However, the mechanism(s) by which these therapies reverse lipid-induced insulin resistance in skeletal muscle is unclear. We determined the effects of 4 weeks of rosiglitazone treatment and exercise training and their combined actions (rosiglitazone treatment and exercise training) on lipid and glucose metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
94
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 52 publications
14
94
2
3
Order By: Relevance
“…Previous reports observed different effects of lipids on AMPK activation in different tissues. Recently, it has been shown that increased FA availability stimulates AMPK activity in skeletal muscle both in vitro and in vivo (10,(24)(25)(26)(27). Likewise, a diminished AMPK phosphorylation in the liver was also supported by previous works showing that TG accumulation in the liver is in association with decreased AMPK activation (27,28).…”
Section: Discussionsupporting
confidence: 66%
“…Previous reports observed different effects of lipids on AMPK activation in different tissues. Recently, it has been shown that increased FA availability stimulates AMPK activity in skeletal muscle both in vitro and in vivo (10,(24)(25)(26)(27). Likewise, a diminished AMPK phosphorylation in the liver was also supported by previous works showing that TG accumulation in the liver is in association with decreased AMPK activation (27,28).…”
Section: Discussionsupporting
confidence: 66%
“…In fact, our preliminary experiments using C2C12 myotubes showed the increment in mtDNA copy number resulting from rosiglitazone exposure to be independent of BNIP3 (data not shown). Also, different PPARγ co-regulators might enable BNIP3 to act in a tissue-specific manner [35,36]. Furthermore, from our bioinformatics analysis, we could find several mitochondria-related proteins that physically interact with BNIP3 [37][38][39] and are expressed differently depending on the type of tissue.…”
Section: Discussionmentioning
confidence: 87%
“…Besides the increase in the amount of mitochondria, it was interesting to note that there was an increase in oxygen consumption and uncoupling, which suggests that BNIP3 enhances mitochondrial function in the adipocytes. The critical differences in the effect of BNIP3 in various tissues might be because of differences in the tissue-specific expression and function of PPARγ [32][33][34], PPARγ coregulators [35,36] and BNIP3-interacting proteins [37][38][39]. In fact, our preliminary experiments using C2C12 myotubes showed the increment in mtDNA copy number resulting from rosiglitazone exposure to be independent of BNIP3 (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Diversos estudos demonstraram que a ingestão de dieta hipercalórica está associada à resistência à insulina em humanos (27) e em animais (28). Tal alteração decorre do aumento expressivo da massa adiposa que induz uma elevação da produção e liberação de proteínas que prejudicam a sinalização da insulina e a expressão de transportadores de glicose em tecidos insulino-sensíveis (2).…”
Section: Discussionunclassified
“…A expressão da proteína GLUT4, tal como a translocação para a membrana plasmática induzida por estí-mulo de insulina, é reduzida pela dieta de alto teor de gordura (28,29). Contrariamente a essas observações, no presente estudo, a dieta hiperlipídica não surtiu efeito significante na expressão de RNAm de GLUT4 nem no conteúdo proteico, porém se observou importante tendência à redução (30%) no grupo OS, quando comparado ao CS.…”
Section: Discussionunclassified